Effect of Maltodextrin on Quality Attributes of Reduced Fat Brownies - สินชัยพานิช รองศาสตรจารย์ ดร.พรรัตน์; เหมวดี พิชญาพร; ดิษนิล ศศพินทุ์; ดิษนิล ศศพินทุ์; ทวิชชาติวิทยากุล ผู้ช่วยศาสตรจารย์เรณู (Journal of Food Health and Bioenvironmental Science, 2017)
The objective of this study was investigated the effect of maltodextrin on quality attributes of reduced fat brownies. Maltodextrin gel (Maltodextrin: water equal to 1:1) was used as a fat substitute in full butter fat brownies at levels of 25, 50 and 75%. Texture attributes, volume, color, water activity, sensory acceptability and reduction of fat content were explored. The results showed that increasing maltodextrin gel increased the cohesiveness (0.16-0.20) but reduced the firmness (8.4-9.2 kg/sec) and springiness (0.41-0.44); full butter fat brownie values were 0.10, 10.1 kg/sec and 0.45, respectively. The cake volume trend declined (p≥0.05). The color values of L*, a* and b* increased according to the appearance of reduced fat brownies presenting as light dark brown. The water activity values of all samples were similar (0.72-0.75). The sensory results showed the scores of overall acceptability, taste and odor declined, except for texture and color, which increased compared to the full butter fat brownie. Higher levels of maltodextrin gel used as fat replacer resulted in reductions of total fat and saturated fat in brownies. Considering the quality of the reduced fat brownie, health benefits and product acceptability, it could be summarized that an appropriated level of maltodextrin gel to use for fat substitution in brownies was less than 50%.